Recent Topics of Pneumococcal Vaccination: Indication of Pneumococcal Vaccine for Individuals at a Risk of Pneumococcal Disease in Adults - Nobuhiro Asai; Hiroshige Mikamo (Microorganisms, 2021)
Pneumococcal disease is one of the most common and severe vaccine-preventable diseases (VPDs). Despite the advances in antimicrobial treatment, pneumococcal disease still remains a global burden and exhibits a high mortality rate among people of all ages worldwide. The immunization program of the pneumococcal conjugate vaccine (PCV) in children has decreased pneumococcal disease incidence in several countries. However, there are several problems regarding the pneumococcal vaccine, such as indications for immunocompetent persons with underlying medical conditions with a risk of pneumococcal disease, the balance of utility and cost, i.e., cost-effectiveness, vaccine coverage rate, serotype replacement, and adverse events. Especially for individuals aged 19–64 at risk of pneumococcal disease, physicians and vaccine providers should make a rational decision whether the patients should be vaccinated or not, since there is insufficient evidence supporting it. We describe this review regarding topics and problems regarding pneumococcal vaccination from the clinician’s point of view.